The Urgency of The Development of Social Studies Learning Through Innovation of Youtube Media as a Source of Learning Media in the Covid-19 Pandemic - Noor Amitasari (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2021)
Reflecting on the training situation in Indonesia during the COVID-19 pandemic, using technology has a significant position in connecting educator and pupil interactions for the gap learning process, which we often name online mastering (in a distance network). Currently, the pandemic is a project in growing creativity within the use of era, no longer most effective transmitting understanding, however additionally the way to ensure mastering is conveyed nicely. Educators want learning media to assist the teaching and to get to know manners. Technological tendencies have a tremendous impact on the training sector, one of which is the usage of Youtube as a medium of facts. In this circumstance, the most suitable way to study is through Youtube media. Educators can use Youtube as a studying medium. This was getting to know media is packaged in the shape of videos that specify social studies fabric the usage of traditional gaining knowledge together with cloth presentation, pattern questions, steps for fixing social studies issues, and giving practice questions. This paper aims to apply Youtube for distance learning and assist students in apprehending the getting to know cloth.